Influence of herbicide glyphosate on growth and aflatoxin B1 production by Aspergillus section Flavi strains isolated from soil on in vitro assay - Barberis, Carla Lorena (2013)
The effect of six glyphosate concentrations on growth rate and aflatoxin B1 (AFB1) production by Aspergillus section Flavi strains under different water activity (aW) on maize-based medium was investigated. In general, the lag phase decreased as glyphosate concentration increased and all the strains showed the same behavior at the different conditions tested. The glyphosate increased significantly the growth of all Aspergillus section Flavi strains in different percentages with respect to control depending on pesticide concentration. At 5.0 and 10 mM this fact was more evident; however significant differences between both concentrations were not observed in most strains. Aflatoxin B1 production did not show noticeable differences among different pesticide concentrations assayed at all aW in both strains. This study has shown that these Aspergillus flavus and A. parasiticus strains are able to grow effectively and produce aflatoxins in high nutrient status media over a range of glyphosate concentrations under different water activity conditions.